Electronically engineering microstructural design for developing advanced steels: An exploration of high Si bainitic steel. (September 2022) - Xing, Xiaolei; Li, Yawen; Meng, Shuo; Shi, Zhijun; Zhou, Yefei; Yang, Qingxiang; Xiao, Jianwei; Zhu, Yuntian; Deng, Chuang
Graphical abstract: Highlight: >Si addition in bainitic steel leads to a novel FCC-to-BCC phase transformation due to large lattice distortion and Jahn-Keller splitting. >ELF in γ-Fe can be increased by Si addition, which in turn improves its thermal stability and stacking fault energy. >Excellent resistance against elastic strain and wear can be achieved in the laser melting bainitic layer with Si addition. >Microstructures of engineering materials can be designed by tailoring their electronic structures. Abstract: Microstructure engineering is essential for developing advanced steels and is often carried out by thermomechanical processing. Here we report the engineering of microstructures of a high Si bainitic steel by tuning its electronic structure. It is experimentally found that the bainitic steel with Si addition processed with laser melting has a complex multiphase microstructure consisting of α-Fe, γ-Fe, ε-martensite, and nano-scale twin boundaries with significantly improved hardness. Furthermore, calculations based on density functional theory show that the observed microstructure is strongly correlated with changes in the electronic structures of Fe atoms around the Si impurities. In particular, electron localization around the Si impurities significantly alters the stacking fault energy, which promotes the formation of ε-martensite and nanoscale twin boundaries, while the Jahn-Teller splitting caused by Si dopants results in a FCC-to-BCC phase transition with a misorientation angle of 8° between the ( 200 ) γ and ( 1 ¯ 1 ¯ 0 ) α . This work suggests that controlling the microstructures by electronic structure engineering has great potential for designing new structural materials with excellent mechanical properties.